The Integration of Eye Tracking Responses for the Measurement of Contrast Sensitivity: A Proof of Concept Study - Zhuang, Yijing; Gu, Li; Chen, Jingchang; Xu, Zixuan; Chan, Lily Y. L.; Feng, Lei; Ye, Qingqing; Zhang, Shenglan; Yuan, Jin; Li, Jinrong (Frontiers in Neuroscience, 2021)
Contrast sensitivity (CS) is important when assessing functional vision. However, current techniques for assessing CS are not suitable for young children or non-verbal individuals because they require reliable, subjective perceptual reports. This study explored the feasibility of applying eye tracking technology to quantify CS as a first step toward developing a testing paradigm that will not rely on observers’ behavioral or language abilities. Using a within-subject design, 27 healthy young adults completed CS measures for three spatial frequencies with best-corrected vision and lens-induced optical blur. Monocular CS was estimated using a five-alternative, forced-choice grating detection task. Thresholds were measured using eye movement responses and conventional key-press responses. CS measured using eye movements compared well with results obtained using key-press responses [Pearson’s rbest–corrected = 0.966, P < 0.001]. Good test–retest variability was evident for the eye-movement-based measures (Pearson’s r = 0.916, P < 0.001) with a coefficient of repeatability of 0.377 log CS across different days. This study provides a proof of concept that eye tracking can be used to automatically record eye gaze positions and accurately quantify human spatial vision. Future work will update this paradigm by incorporating the preferential looking technique into the eye tracking methods, optimizing the CS sampling algorithm and adapting the methodology to broaden its use on infants and non-verbal individuals.